High-light-transmittance self-cleaning coating for surface of photovoltaic module, coating and preparation method of high-light-transmittance self-cleaning coating

By hydrolyzing and condensing the fluorosilicone copolymer formed by polymerizing fluorine-containing monomers and silane-based monomers on the surface of the photovoltaic module, the problem of loss of fluorine-containing chemical substances in the prior art is solved, and a coating with high light transmission, self-cleaning and good hydrophobic properties is achieved, with high efficiency, low cost and environmental protection.

CN120041033APending Publication Date: 2025-05-27SUZHOU INST FOR ADVANCED STUDY USTC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311516395.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

In the prior art, fluorine-containing chemicals are easily lost during construction coating, resulting in environmental pollution, and at the same time, they are complex, expensive and unstable in production.

Method used

By polymerizing the fluorine-containing monomer with the silane monomer, a fluorosilic copolymer is formed, and its structure includes a fluorine-containing hydrophobic chain segment and a silicone anchor segment, which can be hydrolyzed and condensed with the silicate, firmly "locked" in the polymer segment, and reduce fluorine loss.

Benefits of technology

It significantly reduces the loss of fluorine-containing chemicals during coating coating, reduces environmental pollution, and obtains a coating with high light transmission, self-cleaning and good hydrophobic properties, which is highly efficient, low-cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-transmittance self-cleaning coating for the surface of a photovoltaic module, a coating and a preparation method. The high-light-transmittance self-cleaning coating comprises a first component and a second component, the first component comprises a fluorosilicone copolymer, silicate ester and a first organic solvent, the second component comprises a catalyst and a second organic solvent, the fluorosilicone copolymer comprises a fluorine-containing hydrophobic chain segment and a siloxane anchoring chain segment, and the siloxane anchoring chain segment comprises a fluorine-containing hydrophobic chain segment and a siloxane anchoring chain segment. And at least hydrolytic condensation with silicate ester can be carried out. The coating is formed by curing the high-transmittance self-cleaning coating. By synthesizing the fluorosilicone copolymer, the fluorosilicone copolymer can be subjected to hydrolytic condensation with silicate ester, and meanwhile, fluorine-containing chemical substances are firmly locked in a macromolecular chain segment, so that the problem of loss of the fluorine-containing chemical substances in the coating process of the coating is remarkably solved, the pollution to the environment is greatly reduced, and the coating has the characteristics of high efficiency, low cost and environment friendliness; and the water contact angle of the coating reaches 110-130 degrees, and the light transmittance is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photovoltaic module protection, and relates to a high-transparency self-cleaning coating, a coating and a preparation method thereof, in particular to a high-transparency self-cleaning coating suitable for anti-adhesion on the surface of photovoltaic modules, a coating and a corresponding preparation method and application thereof. Background Art

[0002] With the continuous development of technology, the demand for surface coatings is increasing day by day. These surface coatings are designed to improve the performance of materials, especially their properties when in contact with liquids. Hydrophobic coatings are a coating technology that can improve the interaction between an object and water or other liquids by forming a layer of hydrophobic material on the surface of the object, thus enabling a variety of practical applications. In the past, many hydrophobic coating methods have been proposed, including the use of specific chemical substances such as fluorinated silane coupling agents and silicon-based compounds, as well as physical methods such as nanostructured surfaces. For example, patents with publication numbers CN 110982075 A, CN116217935 A, and CN 113930155 A disclose transparent coatings formed by the hydration of fluorinated silane coupling agents and silicate esters, which have good hydrophobic properties and transparent effects. However, since the hydration of fluorinated silane coupling agents and silicate esters occurs during the construction and coating process, and the molecular weight of fluorinated silane coupling agents is relatively small, the synthesis exposed to the environment will inevitably cause the loss of fluorinated chemical substances, resulting in irreversible pollution to the environment.

[0003] In summary, considering that existing methods usually have some defects, such as complex preparation, high cost, environmental unfriendliness, or unstable performance. Therefore, it is necessary to provide a new hydrophobic coating technology with the characteristics of high efficiency, sustainability, low cost, and environmental friendliness to meet the needs of different fields. Summary of the Invention

[0004] The main purpose of the present invention is to provide a high-transparency self-cleaning coating suitable for anti-adhesion on the surface of photovoltaic modules and a preparation method thereof, so as to overcome the deficiency of pollution caused by the loss of fluorinated chemical substances in the prior art.

[0005] Another object of the present invention is also to provide a high-transparency self-cleaning coating suitable for anti-adhesion on the surface of photovoltaic modules, a preparation method and an application thereof.

[0006] To achieve the foregoing invention purposes, the technical solutions adopted by the present invention include: An embodiment of the present invention provides a highly transparent self-cleaning coating for the surface of a photovoltaic module, which includes: a first component and a second component. The first component includes a fluorosilicon copolymer, a silicate ester, and a first organic solvent. The second component includes a catalyst and a second organic solvent. The fluorosilicon copolymer includes a fluorinated hydrophobic segment and a siloxane anchoring segment, and the fluorosilicon copolymer can at least undergo hydrolysis and condensation with the silicate ester.

[0007] In some embodiments, the fluorosilicon copolymer is prepared by a free radical polymerization reaction of a first monomer, a second monomer, and an initiator. The first monomer is a fluorinated monomer, and the second monomer is a silane monomer.

[0008] An embodiment of the present invention also provides a highly transparent self-cleaning coating for the surface of a photovoltaic module, which is formed by curing the aforementioned highly transparent self-cleaning coating.

[0009] An embodiment of the present invention also provides a preparation method for a highly transparent self-cleaning coating for the surface of a photovoltaic module, which includes: successively coating the first component and the second component in the highly transparent self-cleaning coating on the surface of a substrate, enabling the fluorosilicon copolymer and the silicate ester to undergo a hydrolysis and condensation reaction under the action of a catalyst, and at the same time, the material undergoes room temperature curing to form a highly transparent self-cleaning coating for the surface of a photovoltaic module.

[0010] An embodiment of the present invention also provides an application of the aforementioned highly transparent self-cleaning coating for the surface of a photovoltaic module in the field of substrate protection, wherein the substrate includes at least any one of photovoltaic module glass surfaces such as the surface of photovoltaic glass, the surface of building glass, and the surface of an automobile windshield.

[0011] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1) In the present invention, by polymerizing a fluorinated monomer and a silane monomer, and regulating the hydrophobicity of the coating by controlling the fluorine content in the polymer, a highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module with a water contact angle reaching 110° - 130° is obtained; 2) In the present invention, by synthesizing a fluorosilicon copolymer, whose structure includes a fluorinated hydrophobic segment and a siloxane anchoring segment, while being able to undergo hydrolysis and condensation with the silicate ester, the fluorinated chemical substances are firmly "locked" in the polymer chain segments, significantly reducing the loss problem of fluorinated chemical substances during the coating process of the coating, greatly reducing environmental pollution, and making it have the characteristics of high efficiency, low cost, and environmental protection. Detailed Embodiments

[0012] As described above, in view of the deficiency of pollution caused by the loss of fluorine-containing chemical substances in the prior art, the inventors of this case have provided an innovative method and combination through long-term research and a large number of practices to overcome the shortcomings of the prior art and provide a new way to improve the hydrophobic performance. This is mainly achieved through the design of forming a fluorosiloxane copolymer, which firmly "locks" the fluorine-containing chemical substances in the polymer chain segments, significantly reducing the loss of fluorine-containing chemical substances during the coating process of the paint, greatly reducing environmental pollution, and making it efficient, low-cost and environmentally friendly.

[0013] The technical solution, its implementation process and principle will be further explained below.

[0014] The high-transparency self-cleaning coating for the surface of photovoltaic modules (hereinafter also referred to as "the high-transparency self-cleaning coating with anti-adhesion on the surface of photovoltaic modules") provided by one aspect of the embodiments of the present invention includes: a first component and a second component. The first component (hereinafter also referred to as "the first solution") includes a fluorosiloxane copolymer, a silicate ester and a first organic solvent, and the second component (hereinafter also referred to as "the second solution") includes a catalyst and a second organic solvent. The fluorosiloxane copolymer includes a fluorinated hydrophobic chain segment and a siloxane anchoring chain segment, and the fluorosiloxane copolymer can at least undergo hydrolysis and condensation with the silicate ester.

[0015] In some specific embodiments, the high-transparency self-cleaning coating for the surface of photovoltaic modules is composed of the first solution and the second solution. Based on the total mass of the raw materials of the first solution of the high-transparency self-cleaning coating being 100%, the first solution includes 2% - 32% of the fluorosiloxane copolymer, 0.7% - 27.5% of the silicate ester and the first organic solvent, and the second solution includes 5% - 10% of the catalyst and the second organic solvent.

[0016] In some specific embodiments, the sum of the mass contents (i.e., mass ratios) of the first organic solvent and the second organic solvent in all the raw materials of the high-transparency self-cleaning coating for the surface of photovoltaic modules is 65% - 90%.

[0017] In some specific embodiments, the mass content of the fluorosiloxane copolymer in all the raw materials of the high-transparency self-cleaning coating for the surface of photovoltaic modules is generally controlled to be 2% - 32.55%.

[0018] In some specific embodiments, the mass content of the silicate ester in all the raw materials of the high-transparency self-cleaning coating for the surface of photovoltaic modules is generally controlled to be 0.7% - 28%.

[0019] In some specific embodiments, the mass ratio of the fluorosiloxane copolymer to the silicate ester is generally controlled to be 20:80 - 93:7.

[0020] In some specific embodiments, the silicate ester includes any one or a combination of two or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, etc., but is not limited thereto.

[0021] In some specific embodiments, the present invention also provides a method for preparing the above-mentioned hydrophobic fluorosilicone copolymer. The fluorosilicone copolymer is prepared by a free radical polymerization reaction of a first monomer, a second monomer and an initiator. The first monomer is a fluorine-containing monomer, and the second monomer is a silane monomer. By polymerizing the fluorine-containing monomer and the silane monomer, the present invention adjusts the hydrophobic degree of the coating by controlling the fluorine content in the polymer. While achieving the hydrophobic performance, the silicon-containing monomer in the fluorosilicone copolymer can undergo a hydration reaction with the silicate ester, anchoring the fluorosilicone copolymer in the coating, providing a green and environmentally friendly hydrophobic coating without fluorine loss.

[0022] Compared with the patent of hydrolytic condensation of fluorine-containing silane coupling agent on the substrate surface, through the design of forming a fluorosilicone copolymer, the structure of which includes a fluorine-containing hydrophobic chain segment and a siloxane anchoring chain segment, the present invention can not only carry out hydrolytic condensation with the silicate ester, but also firmly "lock" the fluorine-containing chemical substance in the polymer chain segment, significantly reducing the loss problem of fluorine-containing chemical substances during the coating process, greatly reducing environmental pollution, and making it have the characteristics of high efficiency, low cost and environmental friendliness.

[0023] In some more specific embodiments, the first monomer includes any one or a combination of two or more of 2-(perfluorobutyl)ethyl acrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-perfluorohexylethyl acrylate, 1H,1H,2H,2H-perfluorodecyl acrylate, perfluorooctylpropyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, etc., but is not limited thereto.

[0024] In some more specific embodiments, the second monomer includes any one or a combination of two or more of 3-(methacryloyloxy)propyltrimethoxysilane, methacryloyloxypropyltriethoxysilane, 3-trimethoxysilylpropyl acrylate, 3-[tris(1-methylethoxy)silyl]propyl methacrylate, 3-(dimethoxy(methyl)silyl)propyl methacrylate, methacryloyloxypropylmethyldiethoxysilane, 3-(dimethoxy(methyl)silyl)propyl acrylate, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, 3-(methoxydimethylsilyl)propyl methacrylate, 3-(ethoxydimethylsilyl)propyl methacrylate, 1,3-bis(3-(methacryloyloxy)propyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, 3-(methoxydimethylsilyl)propyl acrylate, [dimethoxy(methyl)silyl]methyl methacrylate, (trimethoxysilyl)methacrylate, etc., but not limited thereto.

[0025] In some more specific embodiments, the initiator includes azo initiators and / or organic peroxide initiators, etc.

[0026] Furthermore, the azo initiators include any one or a combination of two or more of azobisisobutyronitrile (AIBN), azobisisoheptonitrile (ABVN), dimethyl 2,2'-azobis(2-methylpropionate) (AIBME), etc., but not limited thereto.

[0027] Furthermore, the organic peroxide initiators include any one or a combination of two or more of benzoyl peroxide (BPO), tert-butyl peroxybenzoate, methyl ethyl ketone peroxide, etc., but not limited thereto.

[0028] As a more preferred solution, the initiator is selected from azobisisobutyronitrile (AIBN) and / or benzoyl peroxide (BPO).

[0029] In some more specific embodiments, based on 100% of the total mass, the raw materials of the fluorosilicone copolymer include 20% - 30% of the first monomer, 20% - 30% of the second monomer, 0.25% - 0.45% of the initiator and the first organic solvent.

[0030] In some more specific embodiments, the temperature of the radical polymerization reaction is 40 - 70 °C, and the reaction time is 3 - 6 hours.

[0031] In some specific embodiments, the catalyst includes any one or a combination of two or more of ethylamine, diethylamine, triethylamine, tripropylamine, trimethylamine, N,N-diisopropylethylamine, triisopropylamine, etc., and triethylamine is preferably used, but not limited thereto.

[0032] In some specific embodiments, the first organic solvent and the second organic solvent each independently include any one or a combination of two or more of petroleum ether, toluene, xylene, ethanol, isopropanol, n-butanol, acetone, methyl ethyl ketone, ethyl acetate, butyl acetate, etc., but are not limited thereto.

[0033] Another aspect of the embodiments of the present invention provides a highly transparent self-cleaning coating for the surface of a photovoltaic module (which can also be referred to as a "highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module"), which is formed by curing the aforementioned highly transparent self-cleaning coating for the surface of a photovoltaic module.

[0034] Furthermore, the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module is composed of the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module, and is a single-layer structure formed by curing the first solution coating with the second solution containing a catalyst.

[0035] In some specific embodiments, the water contact angle of the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module is 110° - 130°. The present invention polymerizes a fluorine-containing monomer and a silane monomer, and adjusts the hydrophobicity of the coating by regulating the fluorine content in the polymer, thereby obtaining a highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module with a water contact angle reaching 110° - 130°.

[0036] In some specific embodiments, the water contact angle of the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module is preferably 115° - 130°.

[0037] In some specific embodiments, the light transmittance of the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module is >99%.

[0038] In some specific embodiments, the thickness of the highly transparent self-cleaning coating with anti-adhesion on the surface of a photovoltaic module is 50 nm - 300 nm, preferably 100 nm - 200 nm.

[0039] Another aspect of the embodiments of the present invention also provides a preparation method for the aforementioned highly transparent self-cleaning coating for the surface of a photovoltaic module, which includes: Coat the first component and the second component in the highly transparent self-cleaning coating on the surface of the substrate in sequence, so that the fluorosilicon copolymer and the silicate undergo a hydrolysis and condensation reaction under the action of a catalyst, and at the same time, carry out room temperature curing to form an anti-adhesion highly transparent self-cleaning coating.

[0040] The coating preparation mechanism of the present invention lies in that: the silicon-containing part (i.e., fluorosilicon copolymer) in the first component, silicate ester, and the hydroxyl groups on the glass surface can undergo hydrolysis and condensation reactions pairwise or directly among the three: both the silicon-containing part and silicate ester can be hydrolyzed to form hydroxyl groups, and the hydroxyl groups can remove small-molecule water under the action of a catalyst to form stable silicon-oxygen covalent bonds. Therefore, not only can fluorine-containing substances be "locked" in the polymer through polymerization reactions, but also fluorine-containing polymers can be "locked" in silicate ester through hydrolysis reactions, making the self-cleaning material more stable and green.

[0041] In some specific embodiments, the room-temperature curing time of the high-transparency self-cleaning coating with anti-adhesion on the surface of the photovoltaic module is more than 10 minutes, preferably more than 30 minutes.

[0042] In some specific embodiments, the coating method includes spraying, specifically including: separately loading the first component and the second component into a closed spray bottle, first spraying the first component containing a hydrophobic fluorosilicon copolymer and silicate ester, and then spraying the second component containing a catalyst to cure the coating.

[0043] In summary, the present invention prepares a high-transparency self-cleaning coating with anti-adhesion on the surface of the photovoltaic module by anchoring silicon-oxygen bonds with a hydrophobic fluorosilicon copolymer, and the prepared transparent coating has good protection and functionality.

[0044] Another aspect of the embodiments of the present invention also provides an application of the aforementioned high-transparency self-cleaning coating for the surface of the photovoltaic module, and this coating is applicable to substrates such as the surface of photovoltaic glass, the surface of building glass, and automobile windshields.

[0045] In order to more clearly elaborate the technical features, objectives, and beneficial effects brought by the present invention, the technical solutions of the present invention will now be explained in detail. Many specific details are set forth in the following description in order to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein. Those skilled in the art can make similar extensions without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0046] Unless otherwise specified, the raw materials and reagents in the embodiments of the present application are all purchased through commercial channels.

[0047] All numerical parameters in the present invention (such as temperature, time, concentration, weight, etc., including their respective value ranges) can generally be appropriately adjusted with an increment or decrement of 0.1 or 1.0. All these numerical parameters can be understood as being preceded by the term "about".

[0048] Example 1 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 70°C in a mass ratio of 62.43:37.08:0.49 to obtain a hydrophobic fluorosilicone copolymer solution after 4 hours.

[0049] Step (b): according to the molar ratio of hydrophobic fluorosilicone copolymer to silicate being 8:92 (mass ratio being 0.278:1), silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (isopropanol) is added, and after mixing evenly, a first solution A1 is obtained for standby use.

[0050] Step (c): Triethylamine and isopropanol are mixed evenly to obtain a second solution B (triethylamine content is 5 wt%) for standby use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 80% by weight of all the raw materials of the high light transmittance self-cleaning coating.

[0051] Step (d): coating the glass substrate with the first solution A1 prepared in step (b) by spraying, and then catalytically curing the glass substrate with the second solution B prepared in step (c) by spraying, and then leaving it at room temperature overnight to obtain a transparent hydrophobic coating.

[0052] Example 2 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 70°C in a mass ratio of 62.43:37.08:0.49 to obtain a hydrophobic fluorosilicone copolymer solution after 4 hours.

[0053] Step (b): according to the molar ratio of hydrophobic fluorosilicone copolymer to silicate being 20:80 (mass ratio being 0.79982:1), silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (isopropanol) is added, and after mixing evenly, a first solution A2 is obtained for standby use.

[0054] Step (c): Triethylamine and isopropanol are mixed evenly to obtain a second solution B (triethylamine content is 5 wt%) for standby use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 70% by weight of all the raw materials of the high light transmittance self-cleaning coating.

[0055] Step (d): coating the glass substrate with the first solution A2 prepared in step (b) by spraying, and then catalytically curing the glass substrate with the second solution B prepared in step (c) by spraying, and then leaving it at room temperature overnight to obtain a transparent hydrophobic coating.

[0056] Example 3 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 70°C in a mass ratio of 62.43:37.08:0.49 to obtain a hydrophobic fluorosilicone copolymer solution after 4 hours.

[0057] Step (b): according to the molar ratio of hydrophobic fluorosilicone copolymer to silicate being 40:60 (mass ratio being 2.133:1), silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (isopropanol) is added, and after mixing evenly, a first solution A3 is obtained for standby use.

[0058] Step (c): Triethylamine and isopropanol are mixed evenly to obtain a second solution B (triethylamine content is 5 wt%) for standby use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 65% of the total mass content of the raw materials of the high light transmittance self-cleaning coating.

[0059] Step (d): The first solution A3 prepared in step (b) is coated on a glass substrate by spraying, and then the second solution B prepared in step (c) is catalytically cured on the glass substrate by spraying, and a transparent hydrophobic coating is obtained after standing at room temperature overnight.

[0060] Example 4 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 70°C in a mass ratio of 62.43:37.08:0.49 to obtain a hydrophobic fluorosilicone copolymer solution after 4 hours.

[0061] Step (b): according to the molar ratio of hydrophobic fluorosilicone copolymer to silicate being 60:40 (mass ratio being 4.799:1), silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (isopropanol) is added, and after mixing evenly, a first solution A4 is obtained for standby use.

[0062] Step (c): Triethylamine and isopropanol are mixed evenly to obtain a second solution B (the content of triethylamine is 5 wt%), for use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 70% by mass in all the raw materials of the high light-transmitting self-cleaning coating.

[0063] Step (d): The first solution A4 prepared in step (b) is coated on a glass substrate by spraying, and then the second solution B prepared in step (c) is used to catalytically cure the glass substrate by spraying. After standing overnight at room temperature, a transparent hydrophobic coating is obtained.

[0064] Example 5 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are in a mass ratio of 62.43:37.08:0.49, and radical copolymerization is carried out at 70 °C. After 4 hours, a hydrophobic fluorosilicon copolymer solution is obtained.

[0065] Step (b): According to the molar ratio of the hydrophobic fluorosilicon copolymer to the silicate ester of 80:20 (mass ratio of 12.797:1), the silicate ester (TEOS) is added to the hydrophobic fluorosilicon copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (isopropanol) is added. After mixing evenly, a first solution A6 is obtained, for use.

[0066] Step (c): Triethylamine and isopropanol are mixed evenly to obtain a second solution B (the content of triethylamine is 5 wt%), for use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 75% by mass in all the raw materials of the high light-transmitting self-cleaning coating.

[0067] Step (d): The first solution A6 prepared in step (b) is coated on a glass substrate by spraying, and then the second solution B prepared in step (c) is used to catalytically cure the glass substrate by spraying. After standing overnight at room temperature, a transparent hydrophobic coating is obtained.

[0068] Example 6 Step (a): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are in a mass ratio of 44.9:53.33:1.76, and radical copolymerization is carried out at 70 °C. After 4 hours, a hydrophobic fluorosilicon copolymer solution is obtained.

[0069] Step (b): According to the molar ratio of hydrophobic fluorosilicon copolymer to silicate ester being 8:92 (mass ratio being 0.3887:1), add silicate ester (TEOS) to the hydrophobic fluorosilicon copolymer solution prepared in step (a), and at the same time add one volume equivalent of the first organic solvent (isopropanol). After mixing evenly, obtain the first solution A7 for later use.

[0070] Step (c): Mix triethylamine and isopropanol evenly to obtain the second solution B (triethylamine content is 5 wt%) for later use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 80% by mass in all the raw materials of the high-transparency self-cleaning coating.

[0071] Step (d): Coat the glass substrate with the first solution A7 prepared in step (b) by spraying, and then catalyze and cure the glass substrate with the second solution B prepared in step (c) by spraying. After standing at room temperature overnight, obtain a transparent hydrophobic coating.

[0072] Example 7 Step (a): The first monomer (2-perfluorohexylethyl methacrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are in a mass ratio of 63.2:36.32:0.48, and carry out free radical copolymerization at 70 °C. After 4 hours, obtain a hydrophobic fluorosilicon copolymer solution.

[0073] Step (b): According to the molar ratio of hydrophobic fluorosilicon copolymer to silicate ester being 8:92 (mass ratio being 0.284:1), add silicate ester (TEOS) to the hydrophobic fluorosilicon copolymer solution prepared in step (a), and at the same time add one volume equivalent of the first organic solvent (isopropanol). After mixing evenly, obtain the first solution A2 for later use.

[0074] Step (c): Mix triethylamine and isopropanol evenly to obtain the second solution B (triethylamine content is 5 wt%) for later use. The sum of the first organic solvent (isopropanol) and the second organic solvent accounts for 85% by mass in all the raw materials of the high-transparency self-cleaning coating.

[0075] Step (d): Coat the glass substrate with the first solution A2 prepared in step (b) by spraying, and then catalyze and cure the glass substrate with the second solution B prepared in step (c) by spraying. After standing at room temperature overnight, obtain a transparent hydrophobic coating.

[0076] Example 8 Step (a): The first monomer (2-perfluorohexylethyl methacrylate), the second monomer (3-(methacryloyloxy)propyltrimethoxysilane), and the initiator (AIBN) are subjected to free radical copolymerization at 70 °C according to a mass ratio of 63.2:36.32:0.48, and a hydrophobic fluorosilicon copolymer solution is obtained after 4 hours.

[0077] Step (b): According to a mass ratio of hydrophobic fluorosilicon copolymer to silicate ester of 0.284:1, the silicate ester (TEOS) is added to the hydrophobic fluorosilicon copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (n-propanol) is added. After mixing evenly, the first solution A2 is obtained for later use.

[0078] Step (c): Triethylamine and n-propanol are mixed evenly to obtain the second solution B (the content of triethylamine is 6 wt%) for later use. The sum of the first organic solvent (n-propanol) and the second organic solvent accounts for 90% by mass in all the raw materials of the high light transmittance self-cleaning coating.

[0079] Step (d): The first solution A2 prepared in step (b) is coated on the glass substrate by spraying, and then the second solution B prepared in step (c) is used to catalytically cure the glass substrate by spraying. After standing overnight at room temperature, a transparent hydrophobic coating is obtained.

[0080] Example 9 Step (a): The first monomer (2-(perfluorobutyl)ethyl acrylate), the second monomer (methacryloyloxypropyltriethoxysilane), and the initiator (AIBN) are subjected to free radical copolymerization at 70 °C according to a mass ratio of 63.2:36.32:0.48, and a hydrophobic fluorosilicon copolymer solution is obtained after 3 hours.

[0081] Step (b): According to a mass ratio of hydrophobic fluorosilicon copolymer to silicate ester of 0.363:1, the silicate ester (TEOS) is added to the hydrophobic fluorosilicon copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (ethanol) is added. After mixing evenly, the first solution A2 is obtained for later use.

[0082] Step (c): Trimethylamine and ethanol are mixed evenly to obtain the second solution B (the content of trimethylamine is 8 wt%) for later use. The sum of the first organic solvent (ethanol) and the second organic solvent accounts for 65% by mass in all the raw materials of the high light transmittance self-cleaning coating.

[0083] Step (d): The first solution A2 prepared in step (b) is coated on the glass substrate by spraying, and then the second solution B prepared in step (c) is used to catalytically cure the glass substrate by spraying. After standing overnight at room temperature, a transparent hydrophobic coating is obtained.

[0084] Example 10 Step (a): The first monomer (2-perfluorohexylethyl methacrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 60° C. in a mass ratio of 63.2:36.32:0.48 to obtain a hydrophobic fluorosilicone copolymer solution after 4 hours.

[0085] Step (b): According to the mass ratio of hydrophobic fluorosilicone copolymer: silicate being 0.816:1, silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (toluene) is added, and after mixing evenly, a first solution A2 is obtained for standby use.

[0086] Step (c): Diethylamine and toluene are mixed evenly to obtain a second solution B (diethylamine content is 9 wt%) for standby use. The sum of the first organic solvent (toluene) and the second organic solvent accounts for 90% by weight of all the raw materials of the high light transmittance self-cleaning coating.

[0087] Step (d): coating the glass substrate with the first solution A2 prepared in step (b) by spraying, and then catalytically curing the glass substrate with the second solution B prepared in step (c) by spraying, and then leaving it at room temperature overnight to obtain a transparent hydrophobic coating.

[0088] Embodiment 11 Step (a): The first monomer (2-perfluorohexylethyl methacrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 40°C in a mass ratio of 63.2:36.32:0.48 to obtain a hydrophobic fluorosilicone copolymer solution after 6 hours.

[0089] Step (b): According to the mass ratio of hydrophobic fluorosilicone copolymer: silicate of 2.177:1, silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (acetone) is added, and the first solution A2 is obtained after mixing evenly for standby use.

[0090] Step (c): N,N-diisopropylethylamine and acetone are mixed evenly to obtain a second solution B (N,N-diisopropylethylamine content is 10wt%) for standby use. The sum of the first organic solvent (acetone) and the second organic solvent accounts for 80% by weight of all the raw materials of the high light transmittance self-cleaning coating.

[0091] Step (d): coating the glass substrate with the first solution A2 prepared in step (b) by spraying, and then catalytically curing the glass substrate with the second solution B prepared in step (c) by spraying, and then leaving it at room temperature overnight to obtain a transparent hydrophobic coating.

[0092] Example 12 Step (a): The first monomer (2-perfluorohexylethyl methacrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are free radical copolymerized at 70° C. in a mass ratio of 63.2:36.32:0.48 to obtain a hydrophobic fluorosilicone copolymer solution after 6 hours.

[0093] Step (b): According to the mass ratio of hydrophobic fluorosilicone copolymer: silicate being 4.899:1, silicate (TEOS) is added to the hydrophobic fluorosilicone copolymer solution prepared in step (a), and at the same time, one volume equivalent of the first organic solvent (ethyl acetate) is added, and after mixing evenly, a first solution A2 is obtained for standby use.

[0094] Step (c): Triisopropylamine and ethyl acetate are uniformly mixed to obtain a second solution B (triisopropylamine content is 10wt%) for standby use. The sum of the first organic solvent (ethyl acetate) and the second organic solvent accounts for 70% by mass of all the raw materials of the high light transmittance self-cleaning coating.

[0095] Step (d): coating the glass substrate with the first solution A2 prepared in step (b) by spraying, and then catalytically curing the glass substrate with the second solution B prepared in step (c) by spraying, and then leaving it at room temperature overnight to obtain a transparent hydrophobic coating.

[0096] Example 13 The present embodiment is different from the embodiment 1 in that the mass ratio of the hydrophobic fluorosilicone copolymer to the silicate is 0.25:1.

[0097] Embodiment 14

[0098] Compared with Example 1, the present embodiment is different in that the mass ratio of the hydrophobic fluorosilicone copolymer to the silicate is 93:7.

[0099] Comparative Example 1 Uncoated blank glass substrate

[0100] Comparative Example 2 Step (1): Mix the silicate (TEOS) and one volume equivalent of the first organic solvent (isopropanol) to obtain a first solution A8 for standby use.

[0101] Step (2): Mix triethylamine and isopropanol at a volume ratio of 2:5 and mix evenly to obtain the second solution B for later use.

[0102] Step (3): Coat the glass substrate with the first solution A8 prepared in step (1) by spraying, and then catalytically cure the glass substrate with the second solution B prepared in step (2) by spraying. After standing at room temperature overnight, a transparent hydrophobic coating is obtained.

[0103] Comparative Example 3 Step (1): The first monomer (2-perfluorohexylethyl acrylate): the second monomer (3-(methacryloyloxy)propyltrimethoxysilane): the initiator (AIBN) are subjected to free radical copolymerization at a mass ratio of 127.321:75.62:1 at 70 °C, and a hydrophobic fluorosilicon copolymer solution is obtained after 4 hours.

[0104] Step (b): Add one volume equivalent of the first organic solvent (isopropanol) and do not add tetraethyl orthosilicate (TEOS). Mix evenly to obtain the first solution A1 for later use.

[0105] Step (c): Mix triethylamine and isopropanol at a volume ratio of 2:5 and mix evenly to obtain the second solution B for later use.

[0106] Step (d): Coat the glass substrate with the first solution A1 prepared in step (b) by spraying, and then catalytically cure the glass substrate with the second solution B prepared in step (c) by spraying. After standing at room temperature overnight, a transparent hydrophobic coating is obtained.

[0107] The inventor of this case characterized the coating test data of the above examples and comparative examples, and the results are shown in Table 1.

[0108] Table 1 Coating test data of Examples 1-12 and Comparative Examples 1-3

[0109] As can be seen from the results in Table 1 above: By controlling the total addition amount of the fluorosilicon copolymer within a reasonable range (3%-10%), an excellent hydrophobic effect can be obtained for the coating. At the same time, the present invention pre-uses a copolymerization method to "lock" the fluorine-containing substance in the polymer chain segment, reducing the fluorine loss during the coating process of the coating, greatly reducing the environmental pollution, and making it have the characteristics of high efficiency, low cost and environmental protection.

[0110] In summary, the present invention prepares a transparent hydrophobic coating without fluorine loss and with self-cleaning ability through a simple process method, which is beneficial to practical applications.

[0111] In addition, with reference to the foregoing embodiments, the inventors of this case also conducted tests using other raw materials, process operations, and process conditions described in this specification, and all obtained relatively ideal results.

[0112] Obviously, the embodiments of the present invention shown above are only intended to illustrate the principles of the present invention, rather than limiting its implementation. Those skilled in the relevant art can make other forms of modifications or changes to the present invention based on the above description. Since it is impossible to list all implementation manners in detail, any technically obvious derivable changes are still protected by the present invention.

Claims

1. A highly transparent self-cleaning coating for the surface of photovoltaic modules, characterized in that, it comprises: a first component and a second component, the first component includes a fluorosilicon copolymer, a silicate ester and a first organic solvent, the second component includes a catalyst and a second organic solvent, the fluorosilicon copolymer includes a fluorinated hydrophobic chain segment and a siloxane anchoring chain segment, and the fluorosilicon copolymer can at least carry out hydrolysis and condensation with the silicate ester.

2. The highly transparent self-cleaning coating according to claim 1, characterized in that: Based on 100% of the total mass of the raw materials, the first component includes 2% - 32% fluorosilicon copolymer, 0.7% - 27.5% silicate ester and a first organic solvent; and / or, based on 100% of the total mass of the raw materials, the second component includes 5% - 10% catalyst and a second organic solvent.

3. The highly transparent self-cleaning coating according to claim 1, characterized in that: The fluorosilicon copolymer is prepared by a free radical polymerization reaction of a first monomer, a second monomer and an initiator, the first monomer is a fluorinated monomer, and the second monomer is a silane monomer; Preferably, the first monomer includes any one or a combination of two or more of 2-(perfluorobutyl)ethyl acrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, 2-perfluorohexylethyl acrylate, 1H,1H,2H,2H-perfluorodecyl acrylate, perfluorooctylpropyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl methacrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate; Preferably, the second monomer includes any one or a combination of two or more of 3-(methacryloyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, 3-trimethoxysilane acrylate propyl, 3-[tris(1-methylethoxy)silane]propyl methacrylate, 3-(dimethoxy(methyl)silanyl)propyl methacrylate, methacryloxypropylmethyldiethoxysilane, 3-(dimethoxy(methyl)silanyl)propyl acrylate, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, 3-(methoxydimethylsilanyl)propyl methacrylate, 3-(ethoxydimethylsilanyl)propyl methacrylate, 1,3-bis(3-(methacryloyloxy)propyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, 3-(methoxydimethylsilanyl)propyl acrylate, [dimethoxy(methyl)silanyl]methyl methacrylate, (trimethoxysilanyl)methacrylate. Preferably, the initiator includes an azo initiator and / or an organic peroxide initiator. Among them, the azo initiator includes any one or a combination of two or more of azodiisobutyronitrile, azodiisoheptonitrile, and dimethyl azodiisobutyrate; the organic peroxide initiator includes any one or a combination of two or more of benzoyl peroxide, tert-butyl peroxybenzoate, and methyl ethyl ketone peroxide. Preferably, the initiator includes azodiisobutyronitrile and / or benzoyl peroxide.

4. The highly transparent self-cleaning coating according to claim 3, characterized in that: Based on 100% of the total mass, the raw materials of the fluorosilicon copolymer include 20% - 30% of the first monomer, 20% - 30% of the second monomer, 0.25% - 0.45% of the initiator, and the first organic solvent; and / or, the temperature of the free radical polymerization reaction is 40 - 70 °C, and the time is 3 - 6 h.

5. The highly transparent self-cleaning coating according to claim 1, characterized in that: The silicate ester includes any one or a combination of two or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and butyl orthosilicate; and / or, the catalyst includes any one or a combination of two or more of ethylamine, diethylamine, triethylamine, tripropylamine, trimethylamine, N,N-diisopropylethylamine, and triisopropylamine. Preferably, the catalyst is triethylamine.

6. The highly transparent self-cleaning coating according to claim 1 or 4, characterized in that: Both the first organic solvent and the second organic solvent independently include any one or a combination of two or more of petroleum ether, toluene, xylene, ethanol, isopropanol, n-butanol, acetone, methyl ethyl ketone, ethyl acetate, and butyl acetate; and / or, the sum of the first organic solvent and the second organic solvent has a mass content of 65% - 90% in all the raw materials of the highly transparent self-cleaning coating; and / or, the mass content of the fluorosilicon copolymer in all the raw materials of the highly transparent self-cleaning coating is 2% - 32.55%; and / or, the mass content of the silicate ester in all the raw materials of the highly transparent self-cleaning coating is 0.7% - 28%; and / or, the mass ratio of the fluorosilicon copolymer to the silicate ester is 20:80 - 93:

7.

7. A highly transparent self-cleaning coating for the surface of a photovoltaic module, characterized in that, it is formed by curing the highly transparent self-cleaning coating for the surface of a photovoltaic module according to any one of claims 1 - 6.

8. The highly transparent self-cleaning coating according to claim 7, characterized in that: The water contact angle of the highly transparent self-cleaning coating for the surface of a photovoltaic module is 110° - 130°, preferably greater than or equal to 115° - 130°; and / or, the light transmittance of the highly transparent self-cleaning coating for the surface of a photovoltaic module is greater than 99%; and / or, the thickness of the highly transparent self-cleaning coating for the surface of a photovoltaic module is 50 nm - 300 nm, preferably 100 nm - 200 nm.

9. The preparation method of the highly transparent self-cleaning coating for the surface of a photovoltaic module according to claim 7 or 8, characterized in that, comprising: The first component and the second component in the anti-adhesion highly transparent self-cleaning coating are successively coated on the surface of the substrate, so that the fluorosilicon copolymer and the silicate undergo hydrolysis and condensation reaction under the action of a catalyst. At the same time, the material is cured at room temperature to form a highly transparent self-cleaning coating for the surface of the photovoltaic module.

10. According to the preparation method described in claim 9, it is characterized in that: the curing time is more than 10 minutes, preferably more than 30 minutes; and / or the coating method includes spraying.

Citation Information

Patent Citations

  • Preparation method of hard hydrophobic coating without solvent addition

    CN110982075A

  • Hydrophobic coating liquid, glass and preparation method thereof

    CN113930155A

  • High-weather-resistance super-hydrophobic polymer as well as preparation method and application thereof

    CN116217935A